A Review of Natural Fiber-Reinforced Polymer Composite Chemical, Physical, and Thermo-Mechanical Properties - Ritesh Koundal; Rajeev Khanduja; Ankush Sharma; Karun Singh (Green Engineering Society, 2023)
The current study reviews provide a brief overview on the properties of natural fiber and natural fiber reinforced composites like chemical, physical, mechanical properties and thermal behavior which is an emerging area in polymer science. The unique properties of these composites are based on the attributes of the individual components, as well as the relative numbers and arrangements of those components within the material system. The widespread acceptance of composites reinforced with natural fibers has attracted many researchers due to its cost, sustainability, low environmental impact and great availability in nature. The processing of natural fibers is not difficult as compared to the production of conventional fibers. In the construction, aerospace, military, building, packaging, consumer products, and transportation industries for ceiling, paneling, partition boards, etc., natural fibers have shown to be a successful substitute for synthetic fiber. Because of these factors, natural fibers are preferred to conventional fibers. However, natural fiber reinforced composites also have some negative aspects such as increased susceptibility to water damage, less durability in the event of a fire, and diminished strength when they are subjected to mechanical stress. In this paper, the overview related to the natural fiber-reinforced composites and their properties is provided.